2011
DOI: 10.1002/jcc.21908
|View full text |Cite
|
Sign up to set email alerts
|

Denaturation of Drew–Dickerson DNA in a high salt concentration medium: Molecular dynamics simulations

Abstract: We have performed molecular dynamics simulation on B-DNA duplex (CGCGAATTGCGC) at different temperatures. The DNA was immerged in a salt-water medium with 1 M NaCl concentration to investigate salt effect on the denaturation process. At each temperature, configurational entropy is estimated using the covariance matrix of atom-positional fluctuations, from which the melting temperature (T(m)) was found to be 349 K. The calculated configuration entropy for different bases shows that the melting process involves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
(59 reference statements)
2
7
0
Order By: Relevance
“…Several experimental studies indicate that indeed left-handed forms of DNA can occur in strongly supercoiled DNA [23,24,30]. Consistent with previous studies on base pair formation and melting [41,42,43] we found also an…”
Section: Plos Onesupporting
confidence: 92%
“…Several experimental studies indicate that indeed left-handed forms of DNA can occur in strongly supercoiled DNA [23,24,30]. Consistent with previous studies on base pair formation and melting [41,42,43] we found also an…”
Section: Plos Onesupporting
confidence: 92%
“…In this context, computer simulations could bring about a major productivity leap, providing thermodynamic and kinetic information on transition intermediates that might escape spectroscopic detection. Indeed, the large amount of molecular dynamics (MD) work on the melting of base pairs in various conditions (13, 2637) suggests that base-pair opening is an asynchronous process, with one base unstacking significantly before the other. However, systematic studies on how the nucleic acid sequence can affect base-pair opening intermediates during the unzipping of ss/ds junctions are lacking.…”
mentioning
confidence: 99%
“…1, it is obvious that the RMSD increases with the increase in temperature. The simulation was performed for 50 ns at a temperatures of 280, 300, 320, 340, 360, 380, and 400 K. Moreover, unlike the other alternative temperatures, a gap in the RMSD can be seen in the last steps of the simulation between T = 340 and T = 360 K. The experimentally measured melting temperature of Dickerson DNA, in the presence of 1 mol/L NaCl, is 341 K. 38 Based on the simulation, the melting temperature obtained by Izanloo et al is reported as 349 K. 31 Schematic snapshots of DNA extracted from the MD simulation at seven different temperatures are shown in Fig. 2.…”
Section: Resultsmentioning
confidence: 86%
“…Area under the curve of the RDF for water hydrogen and negatively charged phosphate oxygen pairs at seven different temperatures for guanine (GUA), cytosine (CYT), thymine (THY), and adenine (ADE) bases. 31 According to the results presented in Table 1, by increasing the temperature, the number of water molecules around the phosphate oxygen atoms decreased but this was not sharp at T m . Therefore, the release of water molecules around the phosphate oxygen atoms could not be responsible for the sharpness of the transition curve, but the hydrogen bonds between the phosphate oxygen atoms and surrounding water molecules could be involved in the stability of .…”
Section: Figmentioning
confidence: 82%
See 1 more Smart Citation